Development of fire safety best practices for rooftops grid-connected photovoltaic (PV) systems installation using systematic review methodology - Mohd Nizam Ong, N.A.F. (Elsevier Ltd, 2022)
Numerous photovoltaic (PV) fire incidents are caused by overheating of PV system components, direct current (DC) arc-fault or hot spot phenomenon. These causes happen mainly due to poor installation practices by the installers. Many PV system installation guides do not emphasise much on the fire hazard during installation. As the PV system is becoming increasingly popular nowadays, it is crucial to establish a specific and comprehensive guideline pertaining to fire safe installation of the system. Therefore, this paper aims to assess and incorporate such fire safety practices from all PV installation guidelines that are publicly accessible. A total of 40 PV installation publications have been systematically reviewed and classified into two categories â design consideration and installation stage. The analysis pointed out a compilation of fire safety practices during PV system installation focusing on residential rooftop applications from the reviewed publications. Although DC isolators have been reported as the top component of PV fire causes, many guidelines do not emphasise the fire hazards involved as well as the things that should and should not be done during installation. The inclusion of a fire safety checklist is suggested as part of the installation guideline. Â© 2021 Elsevier Ltd